Accuracy of ultrasound and behavioral assessment in determining functional features of ovarian cystic structures - Palhão, Miller Pereira; Paganini Filho, Wanderley; Viana, João Henrique Moreira; Guimarães, Cristiano Rodrigues Borges; Figueiredo, Ana Cristina Silva; Ludgero, Bruno Fernandes Alves; Fernandes, Carlos Antônio de Carvalho (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the accuracy of ultrasound and symptomatology in determining functional features of ovarian cystic structures. In 51 Girolando cows, without corpus luteum, the following were evaluated: presence or absence of luteinized tissue on the follicle wall; serum concentrations of progesterone (P4); and animal clinical signals (anestrus or nymphomania). P4 plasma concentrations were considered as the gold standard. Ultrasound evaluation was an accurate (82.4%) method to diagnose the type of follicular cyst. Anestrus is related to the presence of luteinized cysts and high P4 levels. Non‑luteinized cysts are often found in animals with low P4, which exhibit anestrus or nymphomaniac behavior.